The Basics of Educational Podcasting: Enhancing the Student Learning Experience - Jamie S. Foster; Jennifer Larmore; Stephanie A. Havemann (EDIS)
Podcasting has become a well-known way to communicate in the digital age. Many educators are finding ways to use podcasts in the classroom as a learning tool. This document covers the basic equipment, software, and techniques of podcasting, as well as ways to use podcasts in the classroom, with an in-depth example from the University of Florida. This 6-page fact sheet was written by Jamie S. Foster, Jennifer Larmore, and Stephanie A. Havemann, and published by the UF Department of Microbiology and Cell Science, July 2012.